Ministry with persons with mental illness and their families - Albers, Robert H.; Meller, William; Thurber, Steven D. (Fortress Press, 2019)
In Ministry with Persons with Mental Illness and Their Families, Second Edition, psychiatrists and pastoral theologians come together in an interdisciplinary, collaborative effort to ensure accuracy of information concerning the medical dimensions of mental illness, interpret these illnesses from a faith perspective, and make suggestions relative to effective ministry. Readers will learn how science and a faith tradition can not only co-exist but work in tandem to alleviate the pain of the afflicted and affected.